PRAGMATICS STUDY OF INDIRECT SPEECH ACTS IN GOVERNOR - Citra Juwita; Ratih Inayah (PROJECT (Professional Journal of English Education), 2021)
The aim of this paper is to get an overall understanding of indirect speech acts found in some utterances that was delivered by the Governor of West Java, Ridwan Kamil. This research used qualitative descriptive method to get a deep and holistic understanding about indirect speech acts found in some State Address of the Governor. This research is a qualitative description research.  The source of the data in this study is the utterance spoken by West Java governor, Ridwan Kamil. The data analysis technique in this study used pragmatics as the study of speaker meaning as distinct from word or sentence meaning. Based on the data analysis, it can be considered that there are two forms of illocuotionary speech acts that is used. First, the form of illocutionary speech acts found in this speech are categorized as declarative, imperative, and interrogative.  Second, the type of illocutionary speech acts found are assertive, directive, commissive, and expressive. It shows that the speech that was delivered by Ridwan Kamil is very well prepared. In sum,  speech act theory is needed in the philosophy of language not only because it has demonstrated a wide variety of meaningful uses of language, but also for generating insights into underlying problems. Keywords:  Pragmatics, Indirect Speech Act, Governor